2016
DOI: 10.21930/rcta.vol16_num2_art:364
|View full text |Cite
|
Sign up to set email alerts
|

Efectos de la presión de evaporación y la variedad de caña en la calidad de la miel y la panela

Abstract: Para citar este artículo: Prada-Forero LE, Chaves-Guerrero A, García-Bernal HR. Efecto de la presión de evaporación y la variedad de caña sobre la calidad de la miel y la panela. Corpoica Cienc Tecnol Agropecu. 16(2):153-165 ResumenAl implementar el uso de evaporadores múltiple efecto (EME) al proceso panelero, además del ajuste tecnológico, se requiere mantener la calidad del producto. Esta condición develó el desconocimiento de aspectos como el aporte de las diferencias composicionales en las variedades de c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…This is one of the most critical consumer acceptance aspects of UNCS, but it is also one of the most complex variables to control and standardize. Many factors affect color, including the sugarcane variety and its chemical composition (sugars, flavonoids and organic acids), the agro-ecological conditions, the presence of diseases, the type and concentration of the clarifying extracts, the temperature profile, the residence times, and the efficiency of the clarification processes (Demera et al., 2015; Prada-Forero et al., 2015; Asikin et al., 2016; Lara and Clavijo, 2016; Gutiérrez et al., 2018; Rozo, 2017). Nevertheless, this study showed that the manufacturing technology did not affect this feature; on the contrary, the sugarcane variety showed marked significant differences in color parameters evaluated in UNCS samples from varieties CC 8475 and RD 7511 (Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…This is one of the most critical consumer acceptance aspects of UNCS, but it is also one of the most complex variables to control and standardize. Many factors affect color, including the sugarcane variety and its chemical composition (sugars, flavonoids and organic acids), the agro-ecological conditions, the presence of diseases, the type and concentration of the clarifying extracts, the temperature profile, the residence times, and the efficiency of the clarification processes (Demera et al., 2015; Prada-Forero et al., 2015; Asikin et al., 2016; Lara and Clavijo, 2016; Gutiérrez et al., 2018; Rozo, 2017). Nevertheless, this study showed that the manufacturing technology did not affect this feature; on the contrary, the sugarcane variety showed marked significant differences in color parameters evaluated in UNCS samples from varieties CC 8475 and RD 7511 (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…This indicates that the operating conditions during juice clarification in the traditional production facility are more demanding when for example, clarifying mucilaginous extracts (e.g., Guazuma ulmifolia Lamark, Ochroma lagopus SW, or Triumfetta lapull ). Further, this is also the case when adding lime (CaO); although lime is usually added to increase the pH until values around 5.7 ± 0.1 to reduce the formation of reducing sugars (Prada-Forero et al., 2015), this increase contributes to destabilize, agglomerate and remove colloid and pigmented materials that reduce the final UNCS quality. Hence, it seems that a higher amount of lime was added to the juice from the RD7511 variety, as it showed the highest amount of impurities when it came out from the mill (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations